Prairie dogs, plants, and pollinators: tri-trophic interactions affect plant-insect floral visitor webs in shortgrass steppe - Hardwicke, Kelly, author; Detling, James K., advisor; Henk, Shanna Carney, committee member; Kondratieff, Boris C., committee member; Stolhgren, Thomas J., committee member (Colorado State University. Libraries, 2006)
I investigated how black-tailed prairie dogs (Cynomys ludovicianus) altered pollinator habitat, specifically in terms of bare ground cover and floral resources, on northeastern Colorado's Pawnee National Grassland, in 2003 through 2005. I also measured changes in habitat utilization by insect floral visitors on and off prairie dog colonies, and assessed differences in community composition of both entomophilous plants and anthophilous insects. Lastly, I constructed plant-insect visitor webs describing the relative frequency of different interactions on- and off-colonies in 2004 and 2005. Over the entire study, I sampled the plant and insect communities of seven paired colony and off-colony sites on the Shortgrass Steppe Long-term Ecological Research site. On colonies, there was greater cover of forbs and bare ground, more inflorescences/m2 in all three years, more open flowers/m2 in 2004 and 2005, and greater floral biomass presented by the most frequently visited plant species in 2005 (the only year floral biomass was measured). Floral visitation by the insect community and several individual generalist and specialist groups occurred at greater rates on colonies. There is evidence that insect visitation increases with floral biomass patch density, and even mound density, but there were not higher than expected rates of insect visitation given the greater average floral resource densities on prairie dog colonies. On-colony populations of several plant species in 2004 and 2005 experienced greater visitation, but one important floral resource, Opuntia humijusa, was visited more off-colonies. Diversity (H') was greater on colonies for both entomophilous plant species and insect groups in 2004 and 2005, and there was greater plant species and insect functional group richness on colonies in all three years. Mutualistic webs were more complex on colonies, and less dominated by a core of interactions between halictid bee groups and Opuntia. Plant species on colonies were generalized, receiving the highest median number (5.5) of insect visitor groups, but colony insect communities were specialized, visiting the lowest median number (3) of plant species. These results suggest a significant tri-trophic interaction, driven by prairie dogs, which benefits insect floral visitors, including native pollinators. By altering vegetation, prairie dogs influence plant-pollinator networks in shortgrass steppe.
Keywords: ecology; range management